결핵균과 비결핵성항산균 검출에 Real-time PCR의 유용성 - 윤은영; Eun Young Yun; 조수희; Su Hee Cho; 고세일; Se Il Go; 백종하; Jong Ha Baek; 김유은; You Eun Kim; 마정은; Jeong Eun Ma; et al. (Tuberculosis and respiratory diseases, 2010)
Background: The purpose of this study was to evaluate recently developed real-time polymerase chain reaction (PCR) assay kit to detect Mycobacterium tuberculosis (MTB) and nontuberculous mycobacteria (NTM) in respiratory specimens. Methods: We assessed the positive rate of the real-time PCR assay to detect MTB and NTM in 87 culture-positive specimens (37 sputum, 50 bronchial washing), which were performed real-time PCR by using Real-QTM MTB&NTM Kit from January 2009 to June 2009, at Gyeongsang University Hospital. To compare the efficacy with the TB-PCR assay, we evaluated 63 culture-positive specimens (19 sputum, 44 bronchial washing) for MTB or NTM, which were performed TB-PCR by using ABSOLUTETM MTB II PCR Kit from March 2008 to August 2008. Results: Among 87 specimens tested using real-time PCR, MTB and NTM were cultured in 58 and 29, respectively. The positive rate of real-time PCR assay to detect MTB was 71% (22/31) and 92.6% (25/27) in AFB stain-negative and stain-positive specimens. For NTM, the positive rate of real-time PCR was 11.1% (2/18) and 72.7% (8/11) in AFB stain-negative and stain-positive specimens. Among 63 specimens performed using TB-PCR, MTB and NTM were cultured in 46 and 17, respectively. The positive rate of TB-PCR was 61.7% (21/34) and 100% (12/12) in AFB stain-negative and stain-positive specimens. TB-PCR was negative in all NTM-cultured 17 specimens. Conclusion: TB/NTM real-time PCR assay is useful to differentiate MTB and NTM in AFB stain-positive respiratory specimens and it is as effective in detecting MTB with TB-PCR.